2007
DOI: 10.1152/ajpheart.00689.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in PKC-δ upregulation and cardioprotection induced by chronic intermittent hypoxia

Abstract: The aim was to determine whether increased oxidative stress during the adaptation to chronic intermittent hypoxia (CIH) plays a role in the induction of improved cardiac ischemic tolerance. Adult male Wistar rats were exposed to CIH in a hypobaric chamber (7,000 m, 8 h/day, 5 days/wk, 24-30 exposures). Half of the animals received antioxidant N-acetylcysteine (NAC; 100 mg/kg) daily before the exposure; the remaining rats received saline. Control rats were kept under normoxia and treated in a corresponding mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 46 publications
3
67
0
Order By: Relevance
“…Because CIHH preserves intracellular pH during I/R by PKC activation [42,43], it is possible that this mechanism mediates the suppression of I Na/Ca in CIHH-treated rats. Furthermore, it has been shown that an increase in cytosolic ATP stimulates I Na/Ca in cardiac myocytes [44].…”
Section: Discussionmentioning
confidence: 99%
“…Because CIHH preserves intracellular pH during I/R by PKC activation [42,43], it is possible that this mechanism mediates the suppression of I Na/Ca in CIHH-treated rats. Furthermore, it has been shown that an increase in cytosolic ATP stimulates I Na/Ca in cardiac myocytes [44].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, excess ROS accumulation was itself considered injurious because it can cause lipid peroxidation, protein oxidation, DNA damage [6] and intracellular ion deregulation [7], damaging cellular physiological function. However, it is generally accepted at present that ROS may exert beneficial actions [8] because short or moderate durations of ROS generation can result in pre-conditioning protection of the heart [9] against ischemia/reperfusion (I/R) injury [1]. This protective effect is partially due to IH-induced increases in antioxidative capacity for removing excess ROS [10] and improved Ca 2+ handling for attenuating cytosolic Ca 2+ overload [11].…”
Section: Introductionmentioning
confidence: 99%
“…Both complexes produce reactive oxygen species (ROS) on the matrix side and ␤-oxidation of FA can lead to greater release of ROS, mainly from complex I (50). Although the involvement of ROS in protective signaling has been well documented (23,57), it is unknown whether it may play a role in the infarct size reduction in SHR-Cd36.…”
Section: Discussionmentioning
confidence: 99%